2019
DOI: 10.1002/ejp.1518
|View full text |Cite
|
Sign up to set email alerts
|

Consultation prevalence among children, adolescents and young adults with pain conditions: A description of age‐ and gender differences

Abstract: Background Pain is a common complaint presented in healthcare, but most epidemiological pain research has focused either on single pain conditions or on the adult population. The aim of this study was to investigate the 2017 consultation prevalence of a wide range of pain conditions in the general population of young people. Methods We used the Skåne Healthcare Register, covering prospectively collected data on all healthcare delivered (primary and secondary care) to the population in the region of Skåne, sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
1
8
0
1
Order By: Relevance
“…Men and women also differ in the way they respond to pain. For example, women consume more analgesics, consult more often for health conditions, and are more likely to attend pain clinics (Bondesson, Olofsson, Caverius, Schelin, & Joud, 2020;Mahic, Fredheim, Borchgrevink, & Skurtveit, 2015;Paulose-Ram et al, 2003). There are also differences in treatment responses to pharmacological interventions for pain, including a greater vulnerability to side effects in women (Niesters et al, 2010;Planelles et al, 2020).…”
Section: The Gender Context Of Painmentioning
confidence: 99%
“…Men and women also differ in the way they respond to pain. For example, women consume more analgesics, consult more often for health conditions, and are more likely to attend pain clinics (Bondesson, Olofsson, Caverius, Schelin, & Joud, 2020;Mahic, Fredheim, Borchgrevink, & Skurtveit, 2015;Paulose-Ram et al, 2003). There are also differences in treatment responses to pharmacological interventions for pain, including a greater vulnerability to side effects in women (Niesters et al, 2010;Planelles et al, 2020).…”
Section: The Gender Context Of Painmentioning
confidence: 99%
“…26 However, our data are in line with those of a recent primary care study which showed that only 45% of patients had two or more consultations and only 27.1% of patients with a persistent pain condition consulted 4 or more times. 34…”
Section: Suprapatellar Tendinitismentioning
confidence: 99%
“…Anahtar Kelimeler: Ağrı, Kronik Ağrı, Cinsiyet Kimliği, Kültür GİRİŞ Ağrı, insanlık tarihi kadar eski olmakla birlikte ağrı ile baş etmek için insanlar tarih boyunca uğraş vermişlerdir. Ağrı prevelansı incelendiğinde kadınların ağrı deneyimi oranının yüksek olduğu görülmekte ve çoğu ağrı deneyimi türünde yaşla beraber artış olmaktadır [1]. Ağrı işleme ve stresle ilgili sinyal sistemlerinde her seviyede önemli cinsiyet farklılıkları vardır.…”
Section: öZunclassified